Conceptual Model Elements for Mobile Augmented Reality for Engaging Hearing-Impaired Museum Visitors - Baker, Esraa Jaffar; Abu Bakar, Juliana Aida; Zulkifli, Abdul Nasir (2018)
Nowadays, designers are more concern with the issue of engagement and informal learning at museum and gallery sites. This has made studies to focus more on the use of Mobile Augmented Reality (MAR) at museum and gallery sites. However, most of the MAR applications for museum visitors are largely tailored to normal hearing visitors while the hearing-impaired (HI) visitors are not supported. Thus, this study explored design elements of mobile augmented reality for engaging hearing-impaired visitors at museum site, develop the conceptual model of MAR for HI museum visitors’ engagement based on the identified elements and to evaluate the contribution of the MAR for HI on museum visitors’ engagement. The findings of this study that is the proposed the conceptual model for engagement MAR needed for the design of an efficient museum MAR app for hearing impaired visitors’ depending on six elements are critical. These six elements include Aesthetics, Usability, Interaction, Motivation, Satisfaction and Enjoyment. This study argues that for an efficient and engaged Mobile Augmented Reality app for the hearing-impaired community most especially hearing-impaired visitors to museum sites. This finding will help Mobile Augmented Reality designers and developers on how to design an efficient and engaged Mobile Augmented Reality app for the hearing-impaired community at large and museum hearing-impaired visitors’ specifically.